Evaluation of Geogrid Reinforced Sand Bed Performance Under Static and Dynamic Loadings - M., Basavaraju; Gangadhara, S. (AMC Indian Journal of Civil Engineering, 2026)
Geogrid-reinforced Soil (GRS) can improve the bearing capacity and reduce the settlement of foundations and has been widely applied to the treatment and improvement of soft soil foundations. Civil engineering structures are subjected to static load in the foundation and dynamic loads like moving wheel, machine vibration, and seismic loads etc. This paper presents the results of laboratory model tests conducted on a square footing resting on the geogrid-reinforced sand bed under both static and dynamic load. Commercially available biaxial geogrid made up of polypropylene material having square aperture were used in the experimental investigation. The effect of reinforcement distribution parameters like spacing between the reinforcement (S/B) and the reinforcement layers number(N) are used as the testing parameters. The results of experiments are represented in terms of the non-dimensional parameters, for static load condition, Bearing Capacity Ratio (BCR); for dynamic load condition, the Cyclic Resistance Ratio (CRR), and Settlement Ratio (SR). The experimental results clearly demonstrated that these parameters have a significant influence on the performance of Geogrid-reinforced sand bed. In general, the Bearing Capacity Ratio (BCR) and Cyclic Resistance Ratio (CRR) increased and Settlement Ratio (SR) reduced with the increase in the number of reinforcement layers and reduced rein-forcement spacing.